Dissertations and Theses in Top Nursing Publications: A Bibliometric Study - Woods, Stephen; Phillips, Kathleen; Dudash, Andrew (Evidence Based Library and Information Practice)

(untitled) (University of Alberta Library, 2020)
Objective - To investigate the overall prevalence of citations to theses and dissertations, as well as their prevalence in feature articles, editorials, and review articles in top research nursing journals. To evaluate differences between journals and to determine whether there was a change in use over time. Methods - Journals were selected from the Medical Library Association’s Nursing and Allied Health Resource Section’s 2012 Selected List of Nursing Journals. An evaluation was conducted of citations from 3,711 articles published in 2011 and 2018 in 7 top nursing journals. Thesis and dissertation citations were identified and categorized by type of scholarly communication: feature articles, reviews, and editorials. Analysis was conducted for the prevalence of citations for theses and dissertations based on percentage of overall citations and the percentage of articles with a thesis and dissertation citation.Results - Thesis and dissertation citations accounted for 0.41% of all citations. However, 9.43% of the articles contained at least one thesis and dissertation citation. Feature articles contained more thesis and dissertation citations than review articles and editorials. The Journal of Advanced Nursing, Journal of Clinical Nursing, and the Scandinavian Journal of Caring Sciences published a higher percentage of articles with at least one thesis and dissertation citation.Conclusion - The overall use of theses and dissertations in nursing scholarship is comparatively low compared to other forms of scholarly communication. However, this unique form of scholarship viewed from its impact on the percentage of scholarly articles in nursing demonstrates that theses and dissertations have made more of a contribution than previously reported. Our research provides libraries and the nursing academy with empirical evidence for the value of theses and dissertations. It provides librarians and the nursing academy justification for continuing efforts to preserve, enhance access through digital repositories, and to continue to explore strategies to promote the use of theses and dissertations in research.